(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Since gaining independence, India has made continuous efforts to improve its health and demographic indicators. To this end—ranging from the first population policy of 1948 to the health policy of 2017— sustained efforts have been made to ensure universal access to quality healthcare facilities through the development of basic health infrastructure. For this purpose, various committees constituted periodically, as well as international reports, have consistently recommended increasing public health expenditure; likewise, the government has strived to raise health spending in every annual budget, despite limited resources. However, statistics reveal that the actual amount expended falls significantly short of the figures recommended by these policies. Due to this shortfall in public health expenditure, India’s public health system has had to grapple with numerous challenges—most notably, a shortage of adequate facilities in rural and remote areas, alongside a lack of basic medical amenities within existing health centres. This research paper examines the evolving trends and interdependencies between per capita government health expenditure and various demographic indicators by establishing statistical relationships over the period of 2000 to 2022.